Ловушка в Саннивейле - Гапочка Игорь Марленович (издательство ДОСААФ СССР, 1989)
Экземпляры: ф.13 (20160316) / Инвентарный номер: 032590 / Цена: 0.95 / Авт.знак: Г 19 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6